Financial Equilibrium: An analytical study of a sample of commercial banks listed in the iraq stock exchange through 2004 to 2019 (Entrepreneurship Journal for Finance and Business, 2022)
The research aims to test the financial equilibrium in the Iraqi commercial banks, by utilizing a sample of (9) commercial banks listed in the Iraqi Stock Exchange, for the period (2004-2019). Four financial indicators have been chosen, to measure the financial equilibrium are (liquidity index, profitability index, index financial flexibility, solvency index), and the descriptive and analytical approach was used for the data and information contained in the reports and statements of the research sample banks. Moreover, (Excel-2010) and (SPSS.V.22), to test the hypothesis and answer the question related to the problem of the study and reaching the goals, and as the research reached a set of results. the main finding of this study do not suffer from a financial imbalance resulting from weakness in its four dimensions. Furthermore, this research recommend that, the banks should evaluates its financial performance on an ongoing basis, using indicators of financial equilibrium for its importance in the strength of The financial position of any company with financial activity.